The role of the medical departmental library. - Moran, B (1996)
At most academic medical institutions, the first level of library service is provided by health sciences or medical school libraries. For many medical departments, however, these services are also provided by a second-level library, the departmental library. These libraries are usually supported by a specific department, such as surgery, and provide customized services to this sponsor. Departmental libraries continue to play an important role amid the debate over centralized, versus decentralized, library systems. On the basis of a limited survey, this paper describes a representative medical departmental library.